Antibacterial Activity Test of Ethanol Extract Pineapple (Ananas comosus (L.) Merr.) Peel against Growth of Propionibacterium acnes - Fitriyanti Fitriyanti; Muhammad Nur Rahman Hendrawan; Karunita Ika Astuti (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2019)
Pineapple peel (Ananas comosus (L.) Merr.) is waste from the pineapple fruit. The purpose of this study was to determine the content of pineapple peel extract and to antibacterial activity in various concentrations effective in inhibiting the growth of Propionibacterium acnes. The pineapple peel extract is made by using the extraction method in the form of maceration. The method used in the inhibitory test using the three replication samples in each treatment group. The sample consisted of 10 treatment groups ie pineapple peel extract concentration 12.5%, 25%, 37.5%, 50%, 62.5%, 75%, 87.5%, and 100%, as well as positive and negative control. The results obtained from pineapple peel screening contain flavonoid and saponin compounds. The data analysis shows that pineapple peel extract concentrations of 50%, 62.5%, 75%, 87.5%, and 100% had inhibitory zones with the medium-strong category while clindamycin as the control has a strong inhibition zone. The conclusion of this research proves that pineapple peel extract has antibacterial power to P. acnes with effective concentration is 100% with the strong category.